Hubungan antara Manajemen Diri dan Dukungan Sosial dengan Tingkat Burnout di Masa Pandemi Covid-19 pada Mahasiswa FKIP UNS Surakarta - Anisa Nurafidah; Mintasih Indriayu; Harini Harini (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2024)
The purposes of this study were to: 1) determine the relationship between self-management and social support with burnout levels during the Covid-19 period in FKIP students at Sebelas Maret University, Surakarta; 2) knowing the relationship between self-management and burnout levels during the Covid-19 period in FKIP students at Sebelas Maret University Surakarta; 3) find out the relationship between social support and burnout levels during the Covid-19 period for FKIP students at Sebelas Maret University Surakarta. This research is a quantitative research. The population of this study was FKIP UNS students class 2018-2019 who had attended online lectures during the Covid-19 period with a total sample of 361. The sampling technique used is probability sampling with the type of simple random sampling. The data collection technique used a questionnaire. The data analysis technique used is multiple linear regression analysis. The results showed that: 1) there was a significant relationship between self-management and social support with burnout as evidenced by the value of Fcount > Ftable, namely 7,123 > 3,020; 2) there is a significant relationship between self-management and burnout as evidenced by the value of tcount > ttable, namely -2,624 > 1,966; 3) there is a significant relationship between social support and burnout as evidenced by tcount > ttable, namely -2,719 > 1,966,